2009
DOI: 10.1007/s00221-009-1770-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of hands posture on mental rotation of hands and feet in left and right handers

Abstract: The representation of the body in the brain is continuously updated with regard to peripheral factors such as position or movement of body parts. In the present study, we investigated the eVects of arm posture on the mental rotation of hands and feet. Sixteen right-handed and ten left-handed participants verbally judged the laterality of visually presented pictures of hands and feet in two diVerent postural conditions. In one condition they placed their right hand on their right knee and their left hand behind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
104
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 32 publications
(67 reference statements)
18
104
4
Order By: Relevance
“…It is important to note that most studies on mental rotation, including the present one, recruited only right-handed subjects and found faster responses for right stimuli with respect to left ones both in healthy participants [19,22,25,30], and clinical patients [3,29]. The righthanders' preference for right stimuli is also consistent with a recent study that systematically investigated the preference for the "right" stimuli, demonstrating that the effect of laterality is preserved for right-handers (all subjects in the current study were right-handed) but not left-handers [26]. This might be explained by psychophysical evidence that left-and right-handed people have different representation of their own dominant hand [22], and that several factors, such as proprioception, handedness and visual familiarity, can orchestrate together in mental rotation [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is important to note that most studies on mental rotation, including the present one, recruited only right-handed subjects and found faster responses for right stimuli with respect to left ones both in healthy participants [19,22,25,30], and clinical patients [3,29]. The righthanders' preference for right stimuli is also consistent with a recent study that systematically investigated the preference for the "right" stimuli, demonstrating that the effect of laterality is preserved for right-handers (all subjects in the current study were right-handed) but not left-handers [26]. This might be explained by psychophysical evidence that left-and right-handed people have different representation of their own dominant hand [22], and that several factors, such as proprioception, handedness and visual familiarity, can orchestrate together in mental rotation [26].…”
Section: Discussionsupporting
confidence: 91%
“…The effect of postural signals can produce an effect very specific to the mentally manipulated body part [11,26,40]. For example, if people are requested to judge the laterality of hands and feet pictures, while varying the posture of their own hands but not of their feet, then response time varies for hands' judgement but not for feet [25].…”
Section: Introductionmentioning
confidence: 99%
“…A longer preparation time with a fixed thumb might have increased the influence of the participants' own hand posture, potentially eliciting a stronger posture effect. This assumption, however, is contradicted by the finding that in studies in which a posture effect was observed, no adaptation time was applied previous to the experiment, but the posture was adopted only during the experiment [9,10]. In both experiments, medial-over-lateral-advantage (MOLA) was found regularly for stimuli in palmar view, but not for stimuli in dorsal view.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, this finding can be interpreted as pointing towards a general difference between the processing of palmar and dorsal hand stimuli. Ionta and Blanke [10] had found an effect of stimulus orientation only in dorsal view, and concluded that uncommon views (such as the palmar one) should be less sensitive to orientation changes. The results suggest that palmar hand stimuli were processed using a motor strategy, whereas dorsal stimuli were processed using a visual strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance for the present study, premotor cortex and posterior parietal cortex are activated in the RHI (Ehrsson et al, 2004(Ehrsson et al, , 2005 and activation in premotor cortex has been found to correlate with illusion strength. Moreover, RHI and motor imagery have been shown to depend on multisensory mechanisms, including vision and proprioceptive signals (Botvinick and Cohen, 1998;Ionta and Blanke, 2009;Lloyd, 2007) and changes in illusory hand ownership alter the speed of motor imagery . To our knowledge, our results show for the first time at the neural level a strong anatomical overlap between illusory hand ownership and hand motor imagery in the same subjects showing that common structures are recruited for both processes.…”
Section: Shared Spectral and Anatomical Mechanisms Between Motor Imagmentioning
confidence: 99%